AB0041 Possible role of cell apoptosis in the production and release of il-1β induced by pathogenic crystals. (23rd January 2014) - Oliviero, F.; Scanu, A.; Gnoato, M.; Dayer, J.-M.; Agostini, C.; Sfriso, P.; Punzi, L.
Abstract : Background: Direct cell activation by crystals in vitro provokes the release of a number of cytokines and chemokines but not that of IL-1ß whose production and secretion needs the activation of NALP3 inflammasome and that of procaspase 1. It is now clear that a second stimulus in cell culture experiments is needed to prime cells to generate IL-1ß. Such stimulus is mostly represented by the protein kinase C activator, phorbol 12-myristate 13-acetate (PMA) which influences cell differentiation and stimulate monocyte functions including phagocytosis. Objectives: The purpose of this study was to investigate the mechanism though which crystals induce IL-1ß production after PMA stimulation. Methods: Human THP-1 were incubated for 3 hours with different concentrations of PMA (range 0-300ng/ml) or a mixture of IL-1ß/TNFa (0.5/1 ng/ml) and then re-incubated with fresh medium. The day after cells were stimulated with calcium pyrophosphate (CPP) or monosodium urate (MSU) crystals for 24hours. The rate of intact, necrotic and apoptotic cells induced by PMA before crystal stimulation were quantified by surface annexin V-FITC and propidium iodide staining. The levels of IL-1ß were determined in the culture supernatants by enzyme-linked immunosorbent assay while IL-1 expression was quantify by real time PCR. Results: PMA is a potent inducer of pro-IL-1ß mRNA expression in THP1 cells. After 24h from the 3h treatment with PMA, IL-1ß mRNA is about 10 fold and 35 fold higher using PMA at 100 and 300 ng/ml respectively. At the same time high levels of extracellular IL-1ß are observed. PMA also induces a dose-dependent apoptosis in THP-1 cells after 3h treatment. This effect is much more stronger 24 h after the stimulation and using PMA at 300 ng/ml. The pre-treatment of cells with IL-1ß/TNFa did not affect the rate of intact cells and their viability. IL-1ß/TNFa did not stimulate the IL-1ß mRNA expression nor the release of the protein in the supernatants. MSU and CPP crystals used after a cell washout of 24h, induce high IL-1ß release in culture supernatants only after PMA treatment but slightly affect pro-IL-1ß gene transcription. CPP induced a mild increased expression of IL-1ß mRNA in cells pre-treated with IL-1ß/TNFa. The involvement of inflammasome was confirm by using KCl which returned extracellular IL-1ß to control levels. Conclusions: The results of our study show that high concentrations of PMA used in in vitro experiments to reproduce some aspects of crystal-induced inflammation have a strong effect on cell apoptosis and consequently in their viability. The fact that MSU and CPP crystals have a strong effect on IL-1ß protein levels but not on IL-1ß mRNA, and that this effect is evident only in cells pre-treated with PMA and not with IL-1ß/TNF, confirms that crystals may act on inflammasome assembly or directly on caspase-1 activation once pro-IL-1ß transcription has been already induced. Furthermore, the results of our study prompt us to hypothesize that apoptosis may be considered as one of the signals which lead to IL-1ß activation and release by pathogenetic crystals. Disclosure of Interest: None Declared